Gelatin‐Based Capsules through Interfacial Polymerization: Batch and Continuous Flow Synthesis. Issue 10 (5th July 2019) - Bacher, Lisa; Maskos, Michael; Musyanovych, Anna
Abstract: Cross‐linked gelatin capsules were prepared through interfacial polymerization in the inverse miniemulsion, using toluene diisocyanate (TDI) as a cross‐linker. Synthesis was performed in a batch process and in a continuous flow using a static micromixer. The obtained capsules were in the size range between 0.5 and 2 µm. The influence of TDI amount, pH of gelatin solution, and flow rates on the properties of capsules was studied by dynamic light scattering, transmission electron microscopy, and Fourier transform infrared spectroscopy. The thermoresponsive release of the hydrophilic dye sulforhodamine 101 was investigated by fluorescent spectroscopy. Furthermore, gelatin capsules loaded with magnetite nanoparticles were synthesized in a continuous way, showing the potential to produce capsules for drug release triggered by magnetic hyperthermia in large quantities. Abstract : The synthesis of cross‐linked gelatin capsules containing hydrophilic molecules and iron oxide nanoparticles inside the aqueous core is performed in a batch process and in a continuous flow using a static micromixer. The main parameters influencing the continuous formulation process are investigated and the thermoresponsive release is studied as a function of cross‐linking degree.